Mental registration of 2D and 3D visualizations (an empirical study) - Tory, M. (2003 IEEE Conference Visualization, 2003)
2D and 3D views are used together in many visualization domains, such as medical imaging, flow visualization, oceanographic visualization, and computer aided design (CAD). Combining these views into one display can be done by: (1) orientation icon (i.e., separate windows), (2) in-place methods (e.g., clip and cutting planes), and (3) a new method called ExoVis. How 2D and 3D views are displayed affects ease of mental registration (understanding the spatial relationship between views), an important factor influencing user performance. This paper compares the above methods in terms of their ability to support mental registration. Empirical results show that mental registration is significantly easier with in-place displays than with ExoVis, and significantly easier with ExoVis than with orientation icons. Different mental transformation strategies can explain this result. The results suggest that ExoVis may be a better alternative to orientation icons when in-place displays are not appropriate (e.g., when in-place methods hide data or cut the 3D view into several pieces).